Integrasi Teologi Garam dan Terang, Budaya Tongkonan, dan Sosialisasi Digital dalam Pembinaan Generasi Z di Gereja Toraja - Aussie Femy Tangdilintin (STTI Harvest Semarang, 2025)
The formation of Christian character among Generation Z has become an urgent concern for the Toraja Church amid rapid digital advancement, cultural transformation, and moral pluralism. Generation Z lives within a hyperconnected digital ecosystem that reshapes moral reasoning, religious identity, and patterns of faith formation, while traditional church-based discipleship often struggles to respond effectively. This study examines how the Toraja Church embodies its vocation as “salt and light” (Matt. 5:13–16) in shaping the Christian character of Generation Z within the Torajan socio-cultural and digital context. This research employs a systematic literature review of theological, educational, and sociological studies published between 2018 and 2025, analyzed through a thematic-critical approach. The theoretical framework integrates the theology of salt and light, adolescent moral development theory, contextual ecclesiology, and digital faith formation. The findings reveal three core insights. First, Christian character formation among Generation Z is most effective when faith education moves beyond doctrinal transmission toward holistic formation integrating cognitive, affective, and practical dimensions. Second, the interaction between Torajan cultural values and digital media creates moral ambiguity, requiring the church to cultivate ethical digital literacy as part of discipleship. Third, experiential and community-based approaches—such as small groups, social engagement, and participatory digital ministry—significantly strengthen character formation. The novelty of this study lies in proposing an integrative conceptual model that combines Torajan contextual theology, ethical digital literacy, and experience-based community formation, contributing to contextual practical theology and contemporary Christian education. AbstrakPembentukan karakter Kristiani Generasi Z menjadi isu yang semakin mendesak bagi Gereja Toraja di tengah pesatnya kemajuan digital, transformasi budaya, dan pluralisme moral. Generasi Z hidup dalam ekosistem digital yang hiperterhubung, yang membentuk cara berpikir moral, identitas keagamaan, dan pola pembinaan iman, sementara model pembinaan iman gereja yang konvensional kerap menghadapi keterbatasan dalam merespons realitas tersebut. Penelitian ini mengkaji bagaimana Gereja Toraja menjalankan panggilannya sebagai “garam dan terang” (Mat. 5:13–16) dalam membentuk karakter Kristiani Generasi Z di tengah konteks sosial, budaya, dan digital Toraja. Penelitian ini menggunakan metode studi literatur sistematis terhadap kajian teologi, pendidikan iman, dan sosiologi agama yang dipublikasikan pada periode 2018–2025, dengan pendekatan analisis tematik-kritis. Kerangka teoretis yang digunakan meliputi teologi garam dan terang, teori perkembangan moral remaja, eklesiologi kontekstual, dan konsep pembinaan iman digital. Hasil kajian menunjukkan tiga temuan utama. Pertama, pembentukan karakter Kristiani Generasi Z paling efektif ketika pembinaan iman tidak berhenti pada transfer doktrin, tetapi dilakukan secara holistik dengan mengintegrasikan dimensi kognitif, afektif, dan praksis. Kedua, interaksi antara nilai budaya Toraja dan media digital menciptakan ruang ambiguitas moral yang menuntut gereja mengembangkan literasi digital etis sebagai bagian integral dari pemuridan. Ketiga, pendekatan pembinaan berbasis pengalaman dan komunitas—melalui persekutuan kecil, pelayanan sosial, dan pelayanan digital partisipatif—secara signifikan memperkuat pembentukan karakter Kristiani. Kebaruan penelitian ini terletak pada perumusan model konseptual integratif yang menggabungkan teologi kontekstual Toraja, literasi digital etis, dan pembinaan komunitas berbasis pengalaman, yang berkontribusi bagi pengembangan teologi praktis kontekstual dan pendidikan iman di era digital.